Innovating local-related learning content of environmental education for Klong Roi Sai communities in Bandon Bay area - Machimapero, Wachirasag (Kasetsart Journal of Social Sciences, 2021)
This research was purposed to create an innovative local-related learning content of environmental education for Klong Roi Sai Communities in Bandon Bay, based on holistic community cultures, natural resources and local environment. There are four steps of this participatory action research: analysis of community problems, consideration of possible innovation, planning and practices, and follow-up and evaluation. The quantitative data were analyzed by descriptive statistics of frequency, percentage, mean. The qualitative data were analyzed by content analysis to manage natural resources and community environment in Klong Roi Sai Communities. The research results revealed that local people in Klong Roi Sai Communities do fishing and farming for their living. Their natural resources are diverse and highly abundant. However, the communities handled the resources separately, resulting in environmental problems on the communities. There were five indicators to innovate this learning content: awareness, knowledge, attitudes, skills, and participation. The content was divided into academic content and practices. There were 54 people co-developing these five innovative contents. This innovation can be used to effectively reduce problems on natural resources and community environment.